KEWENANGAN MENGADILI OLEH BASWALU ATAS SENGKETA PROSES YANG DI ATUR DALAM PERATURAN KOMISI PEMILIHAN UMUM - Kofi, Angri Dianto; Sihotang, Erikson (Jurnal Aktual Justice, 2024)
Election Abstr is in accordance with what is mandated by the 1945 Constitution of the Republic of Indonesia, then based on the consideration of point (b) of Law no. 7 of 2017, considering: "That it is necessary to regulate general elections as an embodiment of a democratic constitutional system and with integrity in order to guarantee consistency and legal certainty as well as effective and efficient general elections. On the one hand, Bawaslu's authority in resolving process disputes is considered as a solution to a deadlock if there is a problem regarding the decision of the KPU, Provincial KPU, Regency/City KPU which is considered to be detrimental to election participants, or as a result of disputes between election participants, but on the other hand, this authority is also reaped. a number of problems, some of which were due to Bawaslu taking part in the election process which was the subject of the dispute. Normative Legal Research is a legal method or research carried out by examining existing library materials, more aimed at the Legislation and Laws approach by examining all laws and regulations that are properly related to the legal issue being handled to obtain objective law. (Legal Norms), regarding Bawaslu's relative adjudicating authority or adjudicatory authority relating to the authority to receive, examine, try and resolve cases in court. Conclusion Article 4 paragraph (1) Election Supervisory Body Regulation (Perbawaslu) Number 18 of 2018 concerning Amendments to Regulations General Election Supervisory Body Number 18 of 2017 concerning Procedures for Resolving Disputes in the General Election Process, suggests that special judicial institutions created to resolve election cases be more established and that the structure of existing judicial institutions in Indonesia cover all regions of Indonesia. Like the KPUD which is a branch of the KPU, the Provincial Bawaslu which is a branch of the central Bawaslu.